Analisis Kebijakan Pemerintah Kabupaten Tegal Dalam Mengatasi Pencemaran Limbah Industri Logam (Studi Kasus Industri Logam di Desa Pesarean Kecamatan Adiwerna Kabupaten Tegal) - Fitriyani, Dwi Nur; ., Turtiantoro; ., Sulistyowati (Journal of Politic and Government Studies, 2017)
Abstract. A waste which is generated by industrial activities often give environmental pollution which is bad for the environmental as well as public health in surrounding areas, including waste of metal industrial in the Pesarean village sub-district of Tegal Regency of Adiwerna which is became the background of this research. What are the policities that have been formulated by The Government of Tegal Regency and how the management of the environment and the management of waste which is expected to be able to overcome the pollution of waste generated by metal dissolving industrial. A waste that is generated by metal dissolving industrial is a waste of B3 or a waste of dangerous and toxic materials.The research method being used was qualitative approach with the techniques of data collection were observation, interview and study of documents. Informants in this study was the Head of The Environmental Departement of Tegal Regency, Head of Subdivision B3 (toxic and hazardous materials) Departement of Environmental of Tegal Regency, Structuring and Maintenance of Environmental Law Departement of Environmental of Tegal Regency, Head of Subdivision Metal Industry Machinery and Light Industrial and Labor Service of Tegal Regency, PT Lut Putra Solder of Tegal Regency (Administration of PT Lut Putra Solder Production), The Head of The Village of Pesarean Sub District of Adiwerna Regency of Tegal and The Pesarean Villagers Sub District of Adiwerna Regency of Tegal.The result showed that were three policies from the Governmnet of Tegal Regency that have been formulated to overcome the pollution of waste of metal industry. From the three of those policies, there is one policy that does not appropriate to be implemented because what was already examined does not comply with what is happening in the field. Environmental management is done using stated-based approach that is sentralist, while B3 waste management which is generated based on PP No. 101 2014 on managing Waste of Hazardous and Toxic Materials. With this study, it is expected to be able to be used as an input in reviewing the policities that have been formulated by the Government of Tegal Regency and environmental management and waste management which has been done.A recommendation that could be made for the Government of Tegal Regency is to reaffirm a binding regulations for industry subject in order not to do more environmental pollution by carring out socialization in a sustainable way and formulate policities by involving the community in order that the formulated policities are appropriate for the goals and prosperity of the society.Key Words : Waste of B3, Policy, Management